Multimodal prevention of emergence cough following nasal endoscopic surgery under general anesthesia: a double-blind randomized trial - Jing Xu; Pei Sun; Jia-Hui Ma; Dong-Xin Wang; Dong-Xin Wang (Frontiers in Medicine, 2024)
PurposeCough during emergence from anesthesia is a common problem and may cause adverse events. Monotherapy faces uncertainty in preventing emergence cough due to individual differences. We aimed to evaluate the efficacy and safety of multimodal intervention for preventing emergence cough in patients following nasal endoscopic surgery.MethodsIn this double-blind randomized trial, 150 adult patients undergoing nasal endoscopic surgery were randomly allocated into three groups. For the control group (n = 50), anesthesia was performed according to clinical routine, no intervention was provided. For the double intervention group (n = 50), normal saline 3 mL was sprayed endotracheally before intubation, 0.4 μg/kg dexmedetomidine was infused over 10 min after intubation, and target-controlled remifentanil infusion was maintained at an effect-site concentration of 1.5 ng/mL before extubation after surgery. For the multimodal intervention group (n = 50), 0.5% ropivacaine 3 mL was sprayed endotracheally before intubation, dexmedetomidine and remifentanil were administered as those in the double intervention group. The primary endpoint was the incidence of emergence cough, defined as single cough or more from end of surgery to 5 min after extubation.ResultsThe incidences of emergence cough were 98% (49/50) in the control group, 90% (45/50) in the double group, and 70% (35/50) in the multimodal group, respectively. The incidence was significantly lower in the multimodal group than those in the control (relative risk 0.71; 95% CI 0.59 to 0.86; p < 0.001) and double (relative risk 0.78; 95% CI 0.63 to 0.95; p = 0.012) groups; the difference between the double and control groups was not statistically significant (relative risk 0.92; 95% CI 0.83 to 1.02; p = 0.20). The severity of sore throat was significantly lower in the multimodal group than that in the control group (median difference-1; 95% CI −2 to 0; p = 0.016). Adverse events did not differ among the three groups.ConclusionFor adult patients undergoing endonasal surgery, multimodal intervention including ropivacaine topical anesthesia before intubation, dexmedetomidine administration after intubation, and remifentanil infusion before extubation after surgery significantly reduced emergence cough and was safe.